2004
DOI: 10.1080/00140130410001658709
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards traffic safety, driving behaviour and accident involvement among the Norwegian public

Abstract: The present study aims at identifying determinants of risk behaviour and accident involvement in traffic. The results are based on a self-completion questionnaire survey carried out among a representative sample of Norwegian drivers drawn from the driver's licence register. The data was collected in year 2000 and 2001 (n=2614). The questionnaire included measures of attitudes, risk behaviour and involvement in accidents and near accidents. The results showed that attitudes towards traffic safety issues influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
109
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(134 citation statements)
references
References 31 publications
14
109
0
11
Order By: Relevance
“…Romano et al (2012) also identified male drivers to be more likely to be involved in impaired driving and alcohol-related crashes than females. Iversen and Rundmo (2004) revealed that there was a tendency for younger respondents and male respondents to show more negative attitudes towards safety and engage in more 'non-ideal' behaviours in traffic than others do. Yagil (1998) investigated gender and age-related differences in attitudes towards traffic laws and traffic violations and found out that the male drivers and younger drivers reported a lower level normative motivation to comply with traffic laws and a higher commission of traffic violations compared to females and older drivers.…”
Section: Gender and Age Variability In Traffic Attitudes And Violatiomentioning
confidence: 99%
See 4 more Smart Citations
“…Romano et al (2012) also identified male drivers to be more likely to be involved in impaired driving and alcohol-related crashes than females. Iversen and Rundmo (2004) revealed that there was a tendency for younger respondents and male respondents to show more negative attitudes towards safety and engage in more 'non-ideal' behaviours in traffic than others do. Yagil (1998) investigated gender and age-related differences in attitudes towards traffic laws and traffic violations and found out that the male drivers and younger drivers reported a lower level normative motivation to comply with traffic laws and a higher commission of traffic violations compared to females and older drivers.…”
Section: Gender and Age Variability In Traffic Attitudes And Violatiomentioning
confidence: 99%
“…This attitude-behaviourtraffic safety relationship has been an old phenomenon that has been widely analysed with theories such as the Theory of Reasoned Action and the Theory of Planned Behaviour (TPB) in developed countries (Parker et al, 1992;Iversen and Rundmo, 2004;Eiksund, 2009;Forward, 2009b). Attitudes have often been defined to mean tendencies to evaluate an object with some degree of favour or disfavor, expressed in affective, cognitive or behavioral responses (Eagly and Chaiken, 1993).…”
Section: Driving Attitudes Behaviour and Traffic Safety Violationsmentioning
confidence: 99%
See 3 more Smart Citations